The Impact of Physical and Psychological Job Demands on Nurses’ Work-Related Low Back Pain: A Systematic Review and Meta-analysis - Mohamed, Zoelfigar; Al-Natour , Malek (International Journal of Occupational Safety and Health, 2024)
Introduction: In spite of the important advancement in methods and tools associated with nurses’ Work-Related Lower Back Pain (WrLBP) prevention and treatment, there is still poor worldwide understanding of the phenomena of nurses’ WrLBP with high prevalence, therefore, the aim of the current review is to evaluate the significant predictors of nurses’ WrLBP (i.e. physical job demands, psychological job demands). Methods: There are few systematic reviews on the prevalence of nurses’ WrLBP in one place; hence, this study was planned. The overall prevalence of nurses’ WrLBP was evaluated. A systematic search from Google scholar, MEDLINE, Scopus, PubMed, Web of Sciences was carried out and retrieved 37 eligible articles published worldwide from 2000 to 2023. Results: The statistical analysis of data was conducted using MedCalc® software. The overall pooled prevalence of nurses’ WrLBP was (67.051 %, 95%CI: 66.324-67.771; p<0.001). The current review showed a strongly significant correlation between LPB and physical job demands (P<0.001). Similarly, a meta-analysis of these studies revealed a significant correlation between psychological job demands and nurses’ WrLBP (P = 0.037). Conclusion: The study indicated that the prevalence data would help in formulating and strict implementation of control measures in hospital areas to reduce the level of nurses’ WrLBP.